Myocardial PD-L1 Expression in Patients With Ischemic and Non-ischemic Heart Failure - Kushnareva, Ekaterina; Kushnarev, Vladimir; Artemyeva, Anna; Mitrofanova, Lubov; Moiseeva, Olga (Frontiers in Cardiovascular Medicine, 2022)
Objective. Immune checkpoints inhibitors are promising and wide-spread anti-cancer therapy. Despite their efficacy, they could cause cardiotoxicity, a rare but life-threatening event. There are still no well-described predictive factors for cardiovascular immune-related adverse events and information on high risk groups. According to known experimental studies we hypothesized that cardiovascular diseases may increase myocardial PD-L1 expression, which could be an extra target for checkpoint inhibitors and a potential basis for complications development. Methods. We studied patterns of myocardial PD-L1 expression in non-cancer-related cardiovascular diseases: ischemic heart disease (n=12) and dilated cardiomyopathy (n=7), compared to patients without cardiovascular diseases (n=10). Correlation between immunohistochemical data and echocardiographic parameters was assessed. Statistical analyses were performed using R studio version 1.3.1093. Results. In samples from patients with a history of myocardial infarction, PD-L1 membrane and endothelial expression was more prominent and frequent, and cytoplasmic and intercalated discs staining was more localized. Samples from patients with dilated cardiomyopathy displayed faint endothelial, negative membrane staining and more diffuse PD-L1 expression in cytoplasm and intercalated discs. In samples from non-cardiac patients, no convincing PD-L1 expression was observed. We discovered a significant negative correlation between PD-L1 expression and left ventricular ejection fraction and a positive correlation between PD-L1 expression and left ventricular end-diastolic volume. Conclusions. The present findings lay the groundwork for future experimental and clinical studies of the role of PD-1/PD-L1 pathway in cardiovascular diseases. Further studies are required to find patients at potentially high risk of cardiovascular complications associated with immune checkpoint inhibitors therapy.